A C4N4 Diaminopyrimidine Fluorophore. Issue 17 (4th March 2019) - Noda, Hidetoshi; Asada, Yasuko; Maruyama, Tatsuro; Takizawa, Naoki; Noda, Nobuo N.; Shibasaki, Masakatsu; Kumagai, Naoya
Abstract: Invited for the cover of this issue is the group of Masakatsu Shibasaki and Naoya Kumagai at the Institute of Microbial Chemistry (BIKAKEN), Tokyo. The image depicts the C4N4 unit, which harvests photoenergy and radiates a varied palette of lights. Read the full text of the article at 10.1002/chem.201900467 . Abstract : " Given the modular synthetic capability through a single‐step protocol and bioimaging applications compiled in the communication, we hope that the C4N4 fluorophore finds practical opportunities in a broad range of research activities ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 4299 ff. (DOI:10.1002/chem.201900467 ).